Restoration of Alouatta guariba populations: building a binational management strategy for the conservation of the endangered brown howler monkey of the Atlantic Forest - Oklander, Luciana I.; Rheingantz, Marcelo; Rossato, Rafael S.; Peker, Silvana; Hirano, Zelinda M. B.; Monticelli, Cauê; Dada, Aline Naíssa; Di Nucci, Dante L.; Oliveira, Dilmar; de Melo, Fabiano R.; Valença-Montenegro, Mônica M.; Kowalewski, Martin; et al. (Frontiers in Conservation Science, 2024)
The brown howler monkey (Alouatta guariba) is endemic to the Atlantic Forest of eastern Brazil and northeastern Argentina, threatened by extinction due to habitat loss and fragmentation, and hunting. Its reduced and isolated populations dramatically decreased and suffered local extinctions after recent yellow fever outbreaks, recommending the species risk uplist from Vulnerable to Endangered. In Brazil, the species occurs along eight states in sparse populations, including some large protected areas, and is being uplisted to Endangered. Following the National Action Plan for Conservation of the Atlantic Forest Primates and the Maned-sloth, and applying the Guidelines for Reintroductions and other Conservation Translocations (IUCN/CTSG), the Ex Situ Guidelines (IUCN/CPSG) and the One Plan Approach (IUCN/CPSG), a workshop was held on August 2021 to evaluate the need, requisites and roles of an integrated Population Management Program for A. guariba. Such program was developed in June 2022 defining the objectives of (i) restore in situ populations from ex situ populations, prioritizing populations in higher risk to prevent local extinctions, and (ii) establish an ex situ insurance population. This in situex situ integrated management program was approved by ICMBio in February 2023, with actions recommended for all states along the species distribution. In Argentina, the species is Critically Endangered, with a remaining population of 20-50 individuals. Following the National Plan for Primate Conservation in Argentina, in a process similar to that in Brazil, two workshops were held in 2022/2023 to evaluate and define management actions for the long-term recovery of A. guariba. The priorities indicated were (i) reintroduction in ten potential areas in Misionesdue to a lower risk when compared to reinforcement of remaining populations, and (ii) establishing an ex situ management program in Argentinastill non-existent. The progressive collaboration between the initiatives of both countries is promoting the exchange of experiences and the integration of strategies. Here we summarize the planning and management carried out in Brazil and Argentina, highlighting the need forof integrated measures. We debate on the progresses and challenges, proposing next steps for developing and implementing a binational population management program for the conservation of the brown howler monkey.